The role of the Palestinian Ministry of Education in influencing Palestinian students' attitudes toward vocational and technical education from experts’ perspective - Sheikh Ali, Amjad Ziad Hassan (Journal of Educational and Psychological Sciences, 2023)
This study aims at revealing the role of the Palestinian Ministry of Education in influencing Palestinian students' attitudes toward vocational and technical education from experts’ perspective. To achieve this aim, the researcher relied on the descriptive analytical approach to analyzing the phenomenon of Palestinian students’ orientation towards vocational and technical education, and used interviews as a tool to collect information based on the interpretive paradigm. The main promising finding is that the Ministry of Education positively influenced Palestinian students' attitudes toward vocational and technical education through socialization after Palestinian students' attitudes focused on academic education. The Ministry of Education did that by changing societal perspectives toward vocational and technical, updating curricula to meet local community needs, enacting laws to protect students who want to enroll in vocational education to work in their fields, preparing schools’ infrastructure to suit this type of education, hiring new specialized teachers in various vocational and technical education fields. One of the most important recommendations of the study is the need to change the negative perception towards vocational and technical education.
Keywords: vocational education; technical education; role of the Palestinian Ministry of Education